Site fidelity increases reproductive success by increasing foraging efficiency in a marine predator. (6th June 2022) - Rebstock, Ginger A; Abrahms, Briana; Boersma, P Dee
Abstract: Seabirds must find food efficiently in the dynamic ocean environment to succeed at raising chicks. In theory, site familiarity, gained by prior experience in a place, should increase foraging efficiency when prey is predictable, and translate into increased reproductive success, though this is difficult to test empirically. To address this, we examined foraging-site fidelity in Magellanic penguins Spheniscus magellanicus using movement data from 180 individuals tracked during 23 breeding seasons when penguins make repeated trips from their colony to feed chicks. We tested whether chlorophyll-a concentration, as a proxy for ocean productivity, affects foraging-site fidelity. We then tested whether foraging-site fidelity affects foraging efficiency and reproductive success. Mean foraging-site fidelity was higher in years with higher ocean productivity, when fronts had stronger gradients in temperature and chlorophyll, and prey was likely more predictable. When returning to previously visited foraging sites, penguins arrived and returned faster than predicted for a trip of a given distance, leading to lower mean trip durations and more frequent trips in penguins with high site fidelity. Increased foraging efficiency and chick-feeding frequency in turn led to increased chick survival. Our study reveals that foraging efficiency is a key mechanism linking foraging-site fidelity and reproductive success. Abstract : Using 23 years of movement and breeding data for Magellanic penguins, we show that returning to a familiar site to find food increases efficiency and breeding success. Individuals that are more faithful to foraging areas return to their nests quickly, allowing them to make more trips and feed chicks more frequently than less faithful individuals. This in turn allows site faithful individuals to raise more chicks than less faithful individuals.